2013
DOI: 10.1002/chem.201301030
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a [26]Hexaphyrin Bis‐PdII Complex with a Characteristic Aromatic Circuit

Abstract: Not one, but two: Metalation of a mono-Pd(II) hexaphyrin (1) with [Pd(OCOCF3)2] gave a bis-Pd(II) complex (2), which possesses a characteristic 26 π-aromatic circuit with two outer amino-pyrroles within a rectangular molecular framework. Complex 2 was readily deprotonated to afford a dianion, which was regioselectively methylated to give a methyl derivative. A similar methylation reaction of 1 produced a skeletally rearranged product that contained an N-confused pyrrole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…These results may be ascribed to intrinsic instability of 3 associated with the presence of two meso ‐phenyl substituents that destabilize the HOMO level and/or lack of metal coordination ability of 3 . On the other hand, metalations of 3 with PdCl 2 , Pd(OCOCF 3 ) 2 , CoCl 2 , and [IrCl(cod)] 2 , have been also attempted, all of which led to almost complete recovery of 3 . On the basis of these results, it is concluded that the metal coordination ability of 3 is considerably inferior to that of 1 .…”
Section: Methodsmentioning
confidence: 99%
“…These results may be ascribed to intrinsic instability of 3 associated with the presence of two meso ‐phenyl substituents that destabilize the HOMO level and/or lack of metal coordination ability of 3 . On the other hand, metalations of 3 with PdCl 2 , Pd(OCOCF 3 ) 2 , CoCl 2 , and [IrCl(cod)] 2 , have been also attempted, all of which led to almost complete recovery of 3 . On the basis of these results, it is concluded that the metal coordination ability of 3 is considerably inferior to that of 1 .…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5] These macrocycles exhibit rich and novel coordination behavior,i ncluding the formation of homo-and heterobismetal complexes,m agnetic interactions between encapsulated metal centers, and large structural rearrangements upon metalation. [6][7][8][9][10][11][12] The vast structuraldiversity of the metal complexes of expanded porphyrins hasl ed to diverse applications, such as receptors for transition and lanthanide metal ions, [13] sensitizers for photodynamic therapy, [14] magnetic resonance imaging contrast agents, [15] near-infraredd yes, [16] and nonlinearo ptical materials. [17,18] Moreover,m etalation can be seen as ac hemical trigger that is often used to produce Mçbiusa romatic/antiaromatic species in expanded porphyrins.…”
Section: Introductionmentioning
confidence: 99%
“…Molecules 2020, 25, x 3 of 11 treatment of [26]hexaphyrin bis-Pd(II) complex 5 [19] with 5 equivalents of [RuCl2(p-cymene)]2 in the presence of sodium acetate at room temperature gave the same double-decker complex 4 in 71% yield along with triple-decker complex 3 (5% yield). The structure of 4 was determined by X-ray crystallographic analysis as shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%